Inhaled tobramycin solution-associated recurrent eosinophilia and severe persistent bronchospasm in a patient with cystic fibrosis: a case report - Anbar Ran D; Awa Emad; Santos Roberto P (BMC, 2007)
Abstract Background Delivery of tobramycin by inhalation to the lungs of patients with cystic fibrosis (CF) who are infected with Pseudomonas aeruginosa has been proven to be effective and safe. The aerosol administration allows high concentrations of tobramycin to be delivered to the site of infection with limited systemic absorption. In rare patients, systemic absorption of inhaled tobramycin may be significant enough to produce toxic effects, such as renal and vestibular toxicities. Case presentation We report a patient with CF who developed recurrent eosinophilia and severe persistent bronchospasm following repeated administration of preservative-free tobramycin by inhalation, beginning at 16 months of age. Also, he developed similar signs and symptoms when he was administered tobramycin intravenously on one occasion at 5 1/2 years. The patient had a history of environmental allergies. Temporal sequence of his signs and symptoms after each administration of tobramycin (similar to re-challenge testing), and his improvement after discontinuation of the drug strongly suggest an adverse drug reaction. Conclusion Hypersensitivity reaction should be considered in patients who develop recurrent eosinophilia and deterioration of pulmonary function following the use of tobramycin by inhalation or by intravenous administration.